Financial Performance Mediates R&D Intensity and Intangible Assets on Manufacturing Firm Value in IDX - Fernando Africano; Yesita Astarina; Sulastri (CV. Era Digital Nusantara, 2026)
This study examines the mediation of financial performance on the intensity of research and development and intangible assets on the value of manufacturing companies listed on the IDX for the 2015-2020 period. The independent variable in this study is the intensity of research and development which is proxied by the total R&D expenditure divided by the company's sales and intangible assets which is proxied by the comparison of the total market value of equity with the book value of equity. While the dependent variable used is the firm value proxied by Tobins'Q and the intervening variable used is the firm's performance as proxied by ROA. The population in this study were all manufacturing companies listed on the Indonesian stock exchange. The sampling technique used purposive sampling method. The number of samples is 29 companies. The results of this study indicate that the intensity of research and development has a negative effect on financial performance and firm value. Intangible assets have a positive effect on financial performance and firm value, financial performance has a positive effect on firm value, financial performance mediates the effect of research and development intensity and intangible assets on firm value.